Dribbler and Kicker Systems to Small Size Soccer League Robots: A Study and Project to Latin American Robotics Competition - Araújo, Joaquim; de Lima, Marcos; Montarroyos, Caio; Arruda, Luis H.; Silva, Pedro; Pinto, Adam; Souza, Júlia; Cajueiro, João P. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
There is a noticeable lag between Brazilian Teams and Robocup Division A teams in Small Size Soccer League (SSL). One of the main reasons is the difference in the mechanical project and how effective the dribbler and kicker systems conduct and kick the ball to other robots or the goal. This paper describes the process to develop both dribbler and kicker systems to an SSL robot, beginning with a review of Robocup Division A teams and the main Brazilian teams’ projects. A 3D modeling of the dribbler and kicker systems is presented considering innovation effectiveness and space. The systems and models were evaluated via finite element simulation tests. The manufacturing process and its challenges are not in the scope of this paper due to Covid-19 limitations to lab access and will be part of future works. All parts designed are available for public use, allowing other teams to use them, modified or not, on their projects.